Problematika Hukum Shalat Gerhana Saat Tidak Tampak - Umam, Khotibul (Universitas Islam Negeri Mataram, 2022)
Abstract Eclipses are one of the rare natural phenomena. Apart from being a natural phenomenon, the appearance of an eclipse is the cause of the sunnah of the eclipse prayer. This phenomenon can be known by using contemporary methods of reckoning. To get to know more the author will discuss